2002
DOI: 10.1042/bj20020046
|View full text |Cite
|
Sign up to set email alerts
|

Soya phytoestrogens, genistein and daidzein, decrease apolipoprotein B secretion from HepG2 cells through multiple mechanisms

Abstract: Diets containing the soya-derived phytoestrogens, genistein and daidzein, decrease plasma cholesterol in humans and experimental animals. The mechanisms responsible for the hypocholesterolaemic effects of these isoflavones are unknown. The present study was conducted to determine if genistein and daidzein regulate hepatocyte cholesterol metabolism and apolipoprotein (apo) B secretion in cultured human hepatoma (HepG2) cells. ApoB secretion was decreased dose-dependently by up to 63% and 71% by genistein and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 60 publications
(74 reference statements)
6
78
2
6
Order By: Relevance
“…It has been reported that MTP inhibitor treatment is associated with increased degradation of the apoB protein due to its incomplete lipidation (25). Consistent with this, treatment with genistein and naringenin decreased intracellular apoB protein levels and apoB secretion (23,24). In the present study, the 3-h luteolin treatment caused a reduction of intracellular apoB protein levels in HepG2 cells, which was not accompanied by a reduction of apoB mRNA expression, although apoB secretion was reduced (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It has been reported that MTP inhibitor treatment is associated with increased degradation of the apoB protein due to its incomplete lipidation (25). Consistent with this, treatment with genistein and naringenin decreased intracellular apoB protein levels and apoB secretion (23,24). In the present study, the 3-h luteolin treatment caused a reduction of intracellular apoB protein levels in HepG2 cells, which was not accompanied by a reduction of apoB mRNA expression, although apoB secretion was reduced (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…There is evidence that genistein (isoflavone) and naringenin (flavanone) reduce the gene expression and activity of MTP, thereby inhibiting apoB secretion from HepG2 cells (23,24). In the present study, these flavonoids did not suppress the MTP promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…The approximate 13 % decrease in apo B paralleling levels of TC and LDL-C in our patients is in accordance with data showing that the soya phyto-oestrogens genistein and daidzein decrease apo B secretion from HepG2 cells through multiple mechanisms by lowering cholesterol synthesis, cholesterol esterification, microsomal TAG transfer protein, and enhancing LDL-receptor activity 28 . Moreover, soya protein has been suggested to act as a strong antioxidant 29 .…”
Section: Discussionsupporting
confidence: 92%
“…Factors that up-regulate LDL receptor gene include estrogen and phytoestrogen in HepG2 cells and in rat liver [7,13,15]. Moreover the inhibition of mevalonate synthesis may be exerted by plant isoprenoid and genistein on experimental breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the inhibition of mevalonate synthesis may be exerted by plant isoprenoid and genistein on experimental breast cancer [16]. Genistein has been also shown to decrease cholesterol synthesis in cultured HepG2 [7] and inhibits HMG-CoA reductase activity in MCF-7 human breast cancer cells [17]. It has been suggested that the soy proteins enhance the expression of the LDL receptor in cultured human hepatoma cells [26], animals, and hypercholesterolemic Type 2 diabetic patients [24,25].…”
Section: Introductionmentioning
confidence: 99%